The sequence provided is an arithmetic sequence where each term increases by 1. We can express the \( n \)-th term of the sequence with the following formula:
\[ a_n = 61 + n \]
Here's the breakdown:
- The first term (\( n = 1 \)) is \( 61 + 1 = 62 \).
- The second term (\( n = 2 \)) is \( 61 + 2 = 63 \).
- The third term (\( n = 3 \)) is \( 61 + 3 = 64 \).
- And so on.
Now, to find the 62nd term (\( a_{62} \)):
\[ a_{62} = 61 + 62 = 123 \]
Therefore, the answers are:
\[ a_n = 61 + n \] \[ a_{62} = 123 \]